MORPHO-FUNCTIONAL CLASSIFICATION OF NEURONS: HISTOLOGICAL APPROACHES - Rayimkulov Firdavs Azimjon ogli (Modern American Journals, 2025)
Neurons are the fundamental functional units of both the central and peripheral nervous systems. They are classified based on their morphological structure and physiological functions. This article discusses the histological organization of neurons, their morphological and functional classification, and their role in neural activity. In addition, clinical relevance and recent advances in the study of neuronal differentiation and pathology are also reviewed.
Keywords: Neuron, unipolar, bipolar, multipolar, sensory, efferent, interneuron.